1995
DOI: 10.1152/ajpheart.1995.268.6.h2460
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced contractile dysfunction in guinea pig hearts is not mediated by nitric oxide

Abstract: The decreased contraction amplitude of isolated cardiac myocytes from guinea pigs exposed to lipopolysaccharide (LPS) was reported to be partially reversed by nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide synthase (NOS) [Brady, et al., Am. J. Physiol. 263 (Heart Circ. Physiol. 32): H1963-H1966, 1992]. We have tested the potential involvement of NO formation in LPS-induced cardiac depression in the intact heart. Isolated perfused hearts of LPS-treated guinea pigs (4 mg/kg 4 h before organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
4
17
1
Order By: Relevance
“…It has been suggested that myocardial depression during sepsis is largely mediated by cytokine-stimulated NO production [18,19]. In fact, it has been reported that administration of LPS failed to induce iNOS in the myocardium of guinea pig [20]. However, co-administration of SMT did not affect LPS-induced decrease in cardiac index in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…It has been suggested that myocardial depression during sepsis is largely mediated by cytokine-stimulated NO production [18,19]. In fact, it has been reported that administration of LPS failed to induce iNOS in the myocardium of guinea pig [20]. However, co-administration of SMT did not affect LPS-induced decrease in cardiac index in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…The effects of NO on cardiac function alteration in sepsis is controversial between the isolated system studies (37)(38)(39) and the intact heart models (40,41). The similar alteration in Gmax induced by LNA in LPS and control animals in this study suggested that LPS itself did not modify the NO control of myocardial function, as shown elsewhere (42).…”
Section: Critique Of the Modelsupporting
confidence: 63%
“…Parillo et al 35 and Reilly et al 36 first identified myocardial depressant substances in the serum of patients with septic shock. Cardiac dysfunction has since been documented in human volunteers given small doses of bacterial endotoxin 37 and in a variety of animal models, including administration of endotoxin to numerous species [38][39][40][41][42][43][44][45][46] ; intravenous administration of TNF to guinea pigs and dogs 20 -23 ; and implantation of intraperitoneal fibrin clots impregnated with Gram-positive or Gram-negative bacteria, endotoxin, or TNF in dogs. [47][48][49] Blockade of TNF activity prevents cardiac dysfunction after LPS challenge or cutane- …”
Section: Discussionmentioning
confidence: 99%